2018
DOI: 10.1186/s13578-018-0220-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced calcium ion mobilization in osteoblasts on amino group containing plasma polymer nanolayer

Abstract: BackgroundBiomaterial modifications—chemical and topographical—are of particular importance for the integration of materials in biosystems. Cells are known to sense these biomaterial characteristics, but it has remained unclear which physiological processes bio modifications trigger. Hence, the question arises of whether the dynamic of intracellular calcium ions is important for the characterization of the cell–material interaction. In our prior research we could demonstrate that a defined geometrical surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…with 100 nm Ti particles obtained from the Center for Microtechnologies (ZFM, University of Technology Chemnitz, Germany) at 1 × 1 × 0.075 cm in size (length × width × depth) for cell analysis, or 2 × 1 × 0.075 cm for ζ-potential analysis as previously reported (Staehlke et al, 2018).…”
Section: Functionalization Of Titanium Arraysmentioning
confidence: 99%
“…with 100 nm Ti particles obtained from the Center for Microtechnologies (ZFM, University of Technology Chemnitz, Germany) at 1 × 1 × 0.075 cm in size (length × width × depth) for cell analysis, or 2 × 1 × 0.075 cm for ζ-potential analysis as previously reported (Staehlke et al, 2018).…”
Section: Functionalization Of Titanium Arraysmentioning
confidence: 99%
“…21,22 As such, the tailoring of surface chemicals such as in the case of covalent graing of functional groups or biomolecules without the hindrance of the detachment is a promising alternative to coating techniques. Our groups and others have reported that implants with incorporated functional groups such as carboxyl, 23,24 sulfonic groups, 25 amino 26 and phosphonate groups, 27,28 or biomolecules such as RGD peptides 29 and antimicrobial peptides 30 exhibit up-regulated bone cells osteogenic activity in vitro and osseointegration in vivo.…”
Section: Introductionmentioning
confidence: 95%
“…Test 1 : For the determination of cell adhesion and osteoblast viability, osteoblasts were cultured on the PLGA experimental (HA, SiO 2 , TiO 2 ) and PLGA control membranes, in triplicate, plating 120,000 cells. At 24 h, the cultures were analysed by the microphotography of osteoblasts [ 16 , 17 , 18 ]. Previously, the cells had been fixed with 70% ethanol for 5 min, as it was not possible to observe them without prior fixation.…”
Section: Methodsmentioning
confidence: 99%